Effects of group psychological intervention combined with pulmonary rehabilitation exercises on anxiety and sleep disorders in patients with mild coronavirus disease 2019 (COVID-19) infections in a Fangcang hospital. Issue 2 (7th February 2022) - Liu, Ying; Yang, Yan-Qing; Liu, Yan; Pei, Sheng-Li; Yang, Hui-Hui; Wu, Jia-Jia; Luo, Cai-Kui
ABSTRACT: Fangcang hospitals, as tentative hospitals built to treat a huge turnover of patients with mild coronavirus disease 2019 (COVID-19) infections, have played a pivotal role to slow down the pandemic spread in China in 2020. However, anxiety and sleep disorders remain tough to address during the treatments. In this study, group psychological intervention in combination with pulmonary rehabilitation exercises were conducted in the trial group for the patients with mild COVID-19 infections in a Fangcang Hospital to mitigate the patients' anxiety and sleep disorders, while conventional nursing methods were done in the control group, with 70 randomly picked patients in each group. Effects were assessed through questionnaire method using state anxiety questionnaire (SAI) and Pittsburgh sleep quality index scale (PQSI) rating investigation. Results showed that both SAI and PSQI scores of the trial group were significantly lower than those of the control group (P < 0.05). The SAI scores of the trial group and the control group were 38.5 ± 13.2 and 45.8 ± 10.4 points (t = 3.600, P < 0.001), respectively, and the PSQI scores were 5.6 ± 3.0 and 7.1 ± 3.0 points (t = 2.982, P < 0.01), respectively. Our methods have significant advantages over conventional nursing methods to mitigate anxiety and sleep disorders for the patients with mild COVID-19 infections in the Fangcang Hospital.